Meningkatkan Hasil Belajar Muatan PPKn Menggunakan Model Pembelajaran PBL, STAD, dan Talking Stick Pada Siswa Kelas IV SDN Kelayan Timur 5 Banjarmasin - Yasmin Pitiyanova; Ahmad Muhyani Rizalie (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The problem raised in this study is the low learning outcomes of fourth grade students at SDN Kelayan Timur 5 Banjarmasin on PPKn content. The causes of these problems are learning that does not trigger students' skills in critical thinking, learning is only centered on teachers and theme books, and lack of motivation and interest in student learning. The effort made to address this issue is by using a combination of PBL, STAD, and Talking Stick models. The research aims to describe the quality of teacher and student activities, as well as analyze the improvement in students' learning outcomes. A qualitative approach with Classroom Action Research (CAR) was conducted for three meetings at SDN Kelayan Timur 5 Banjarmasin during the 2022/2023 academic year, involving 25 fourth grade students. The research was carried out on the theme "The Beauty of Diversity in My Country" in the subject of Civics. The data collected included teacher activities, student activities, and students' learning outcomes, which were analyzed using percentage scales and classical learning achievement indicators. The results showed that the combination of PBL, STAD, and Talking Stick models in the third meeting resulted in excellent teacher activities with a score of 98, highly active student activities with a score of 100%, and cognitive and affective learning outcomes reaching 100% proficiency. Based on the findings, it can be concluded that using this combination of teaching models can enhance teacher activities, student engagement, and learning outcomes in the subject of Civics, "The Beauty of Diversity in My Country." Teachers are advised to utilize this combination of models to create learning activities that enhance student motivation, interaction, and engagement, leading to improved student learning outcomes